Boron-doped nanocrystalline diamond grown on reticulated vitreous carbon: Morphological, structural, and electrochemical characterizations - Oishi, S. S.; Botelho, E. C. [UNESP]; Rezende, M. C.; Cairo, C. A.A.; Baldan, M. R.; Ferreira, N. G. (The Electrochemical Society, 2014)
Composites formed from diamond grown on carbonaceous materials have been showed special attention due to their remarkable properties for electrochemical applications. In this sense, boron-doped nanocrystalline diamond (BDND) films were grown on reticulated vitreous carbon (RVC) substrates produced from poly(furfuryl alcohol) at two heat treatment temperatures (HTT) of 1000 °C and 1700 °C. The films were produced from hot filament chemical vapor deposition reactor with an in-situ doping process in the gas phase. Scanning electron microscopy and Raman spectroscopy analyses confirmed that both RVC electrodes were totally covered by good quality nanodiamond coatings with acceptor concentrations at around 1020 B.cm-3, evaluated by Mott- Shottky measurements. Both RVC/BDND composites presented good electrochemical response in redox couple. Nonetheless, RVC/BDND1700 showed the best conductivity due to its lowest variation of ΔEp value as well as its highest electrochemical area. These results demonstrate that RVC/BDND1700 is a very promising electrode material.